Effects of testicular microlithiasis on Doppler parameters: report of three cases - Kutlu, Ramazan (BioMed Central, 2002)
BACKGROUND: Testicular microlithiasis is a rare, usually asymptomatic, non-progressive disease of the testes associated with various genetic anomalies, infertility and testicular tumors. According to our literature search, there is no specific data about Doppler findings in this disease. CASE PRESENTATION: Doppler findings of three cases of testicular microlithiasis during last two years in our institution are presented. CONCLUSIONS: Although our hypothesis was to find increased Doppler parameters due to intratesticular arterial compression, our findings suggest that there are no Doppler findings specific to testicular microlithiasis.